The shape of water - Toro, Guillermo del, 1964-; Hawkins, Sally, 1976-; Shannon, Michael, 1974-; Jenkins, Richard, 1947- (Beverly Hills, California Twentieth Century Fox Home Entertainment, 2018)
In a secret government laboratory, a mute custodian befriends an amphibian human-like creature.
Originally released as a motion picture in 2017.
Bonus DVD includes standard definition version of film.
Sally Hawkins, Michael Shannon, Richard Jenkins, Octavia Spencer, Michael Stuhlbarg.
MPAA rating: R.
The Blu-ray disc can only be played on Blu-ray disc players and will not play on standard DVD players.
110340
Keywords: Amphibians as laboratory animals -- Drama; Mute persons -- Drama; Drama; Fiction films; Adventure films; Fantasy films; Feature films